Pengaruh Birth Ball terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif di PMB Karmila Tahun 2023 - Heni Heriyeni; Rizki Natia Wiji (Lembaga Pengembangan Kinerja Dosen, 2023)
Birth Ball is a birth ball that can be used by mothers in labor in the first stage to a position that can help progress labor. The purpose of this study was to determine the effect of the Birth Ball on reducing the intensity of labor pain during the first active phase. The type of research used in this study was a quasy experiment. The research was conducted at PMB Karmila, Bantan District. The population in this study were all third trimester pregnant women. The sample in this study were 20 pregnant women using purposive sampling. Data analysis was carried out univariately, bivariately using the T-Dependent statistical test (paired T-Test). The results showed that there was an effect of birth ball on the intensity of labor pain in the first stage. to the community, especially primigravida women who experience labor pain to be able to do birth ball therapy to reduce the level of pain in the first stage of labor.\